The national space and borders as variables in international relations and foreign policy: The specificity of territorial negotiations - Rodríguez Cuadros, Manuel (2020)
Territoriality is an essential variable of relationships international and foreign policy. The territory, including its projection maritime, condition and influence relations between States. The power, strategic, political, economic-commercial relations and everything type of international interaction refers directly or indirectly to the National space of the States. In this perspective, the dynamics of cooperation and conflict they have in the territory and their material expressions and legal, such as sovereignty, limits, borders, its areas of action more linked to national interests, conscience and identity national. Their importance in international action gives them regulations constitutional laws that limit and regulate foreign policy decisions referred to these permanent national interests. Conflict is a privileged dynamics of territoriality. Especially in their bonding with the limits and factors that define national identity. The author analyzes all this problematic and links it to types of interstate conflict and various non-jurisdictional dispute settlement mechanisms, with an emphasis on the analytical description of the specificities of the negotiation territorial.